The evidence‐based practices for children, youth, and young adults with autism report: Concerns and critiques. (8th February 2021) - Leaf, Justin B.; Sato, Sara K.; Javed, Asim; Arthur, Shannon M.; Creem, Ashley N.; Cihon, Joseph H.; Ferguson, Julia L.; Oppenheim‐Leaf, Misty L.
Abstract: For individuals diagnosed with autism spectrum disorder (ASD) to make meaningful progress comprehensive intervention using evidence‐based practices is required. To assist with this, the National Clearinghouse on Autism Evidence and Practice (NCAEP) recently published the Evidence‐Based Practices for Children, Youth, and Young Adults with Autism Report (Steinbrenner et al., 2020). The purpose of the NCAEP report was to provide consumers with a list of interventions that have evidence of positive effects for individuals diagnosed with ASD. The NCAEP report identified 28 interventions that were considered evidence based. Given the broad nature and visibility of the NCAEP report, it may be useful to review and discuss any potentially problematic aspects of the methods and results of the NCAEP report to help inform future updates and consumers in interpreting the findings and recommendations within the NCAEP report. Thus, the purpose of this paper is to provide a review of the Evidence‐Based Practices for Children, Youth, and Young Adults with Autism report and provide recommendations to behavior analysts in regard to the report.